The Urgency of Principal's Academic Supervision on PAUD Learning Management - Nurazila Sari; Erni Munastiwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The Urgency of Principal's Academic Supervision on PAUD Learning ManagementThe purpose of this study was to see whether the principal of Annur Kids Kindergarten Pekanbaru had carried out academic supervision and what were the results of the academic supervision. This research is a qualitative research with the type of case study research. The strategy used is an interview by asking five